Gender in the Hindu nation RSS women as ideologues - Bacchetta, P. (Paola) (New Delhi Women Unlimited, 2004)
On the political role and Hindu sentiments of women members of Rashtriya Swayam Sevak Sangh, an Indian political party; articles.
Keywords: Women -- Political activity -- India; Women in Hinduism -- India